Analysis Of Innovation “Puber Anak Melania” In Acceleration Of Birth Certificate Ownership For Children 0-18 Years In The Dinas Kependudukan Dan Pencatatan Sipil Kota Payakumbuh Using Grounded Theory - Gusmeri, Gusmeri; Desmalina, Desmalina; Harsemarozi, Harsemarozi; Heikal, Jerry (CV. ITTC INDONESIA, 2023)
“Puber Anak Melania” is a Program of the Payakumbuh City Government, in this case the Population and Civil Registration Office as a new innovation in providing convenience in obtaining family cards, birth certificates and baby identity cards for the people of Payakumbuh City. It is an acronym for